Refluksna bolezen požiralnika, peptična razjeda in okužba s Helicobacter pylori - prospektivna, kontrolirana raziskava - Skok, Pavel (Zdravniški vestnik, 2003)
Background. A possible association of esophageal reflux disease with peptic ulcer, Helicobacter pylori infection or the results of eradication, has not been elucidated. It is an alarming fact that in developed countries the incidence of esophageal adenocarcinoma, which is associated with reflux disease, is increasing. Aim. The aim of the study was to establish the prevalence of esophageal reflux disease after eradication of H. pylori infection in patients with hemorrhaging and nonhemorrhaging peptic ulcer of stomach or duodenum. Patients and methods. Study was approved in 1998 by the Slovenian Medical Ethics Committee (No. 90/09/98). Prospective, controlled and randomized, carried out between 1998-2000. The study included 80 patients (50 male and 30 female, av. age 57.5 years, SD +/- 17.1, range 22-80 years) in which endoscopy confirmed hemorrhage from peptic ulcer of stomach or duodenum and HP infection. The control group was made up of 80 patients (50 male and 30 female, av. age 56.8 years, SD +/- 16.8, range 19-80 years) with peptic ulcer of stomach or duodenum and H. pylori infection in the same period of time. In all cases the recommended drug combination were used in the treatment of the infection: a proton pump inhibitor, omeprazol (4 weeks), and combination of antibiotics , claritromycin and metronidazole or with regard to the antibiogram (1 week). The therapeutic success was ascertained endoscopically four weeks after inclusion in the study. Infection eradication was confirmed by the rapid urease test and histologic investigation of the gastric mucosa. One year after, in the course of follow-up, in patients with endoscopic investigations, 24-hour pH-metry or fiberoptic spectrophotometric bilirubin determination, bilimetry, we tried to establih signs of esophageal reflux disease. Results. Four weeks after inclusion in the study the success of infection eradication was 92.5% in the study group while in the control group reached 91.25%, p>0.05. Endoscopic investigation performed one year after inclusion in the study revealed a recurrence of H. pylori infection in 4 patients (5%, 4/80) from the study group and in 5 (6.25%, 5/80) from the control group, p>0.05. During endoscopy we confirmed esophagitis in 8 patients from the study group (8/76, 10.5%) and in 9 patients (9/75, 12%) from the control group, p>0.05. The findings of the 24-hour pH-metry confirmed acid reflux in 11 patients (11/76, 14.4%) from the study group and in 10 patients (10/76, 13.1%) from the control group, p>0.05. Fiberoptic spectrophotometric bilirubin determination showed alkaline reflux in 3 patients (3/76, 3.9%) from the study group and in one patient (1/75, 1.3%) from the control group, p>0.05. Conclusions. The results confirm that after eradication of H. pylori infection, esophageal reflux disease occurs significantly more often in patients with peptic ulcer of the duodenum as compared to those with peptic ulcer of the stomach. The development complications is not affected by whether the peptic ulcer had manifested itself with complications or not.
Keywords: Gastroesophageal reflux; Helicobacter pylori; Infection; infekcije; Peptic ulcer; peptični ulkus; požiralnik; refluksna bolezen